The Effect of Self Directed Learning on Students' Academic Procrastination Attitudes - Siregar, Rahma Hayati; Nasution, Ja'far; Sari, Lili Nur Indah; Hoiriyah, Diyah (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2025)
This study aims to determine the effect of Self Directed Learning on academic procrastination attitudes in students. Self Directed Learning is an individual's ability to manage the learning process independently, while academic procrastination is the tendency to postpone academic tasks. This study uses a quantitative approach with a correlational method. Samples were taken from junior high school students using cluster random sampling. Data were collected through questionnaires that had been tested for validity and reliability, then analyzed using the Mann Whitney U Test. The results showed that there was no significant effect of students who applied Self Directed Learning on students' procrastination attitudes. However, there was a decrease in academic procrastination attitudes in mathematics in students who applied Self Directed Learning, which can be seen from the average value of students' procrastination attitudes